A systematic review and meta-analysis of the relationship between genes and reflexive attention - Spencer Myres; Katherine E. Christensen; Rebecca A. Lundwall (Frontiers in Neuroscience)
Defined as the semi-autonomous orientation to either a moving or rapidly appearing stimulus, reflexive attention (RA) is a crucial process for humans. While there are multiple outcomes used to assess RA, their relationships have not been tested. Disruptions in RA often relate to neurodevelopmental disorders, such as attention-deficit/hyperactivity disorder or autism spectrum disorder, so RA might be moderated by age. Additionally, the current academic consensus is that multiple genes influence RA, but this has not been assessed in a meta-analysis. A better understanding of RA using previously collected data will allow us to improve the design of future research studies.MethodsIn accordance with PRISMA, we conducted a broad search for potentially relevant articles pertaining to genes associated with RA. Selected studies included those (1) published in English, (2) involving human participants, and (3) referencing specific genetic markers in association with a measure of RA. For subgroup comparisons, we analyzed 14 studies assessing children and 23 assessing adults. We also compared 18 dopamine-related to 19 non-dopamine related studies.ResultsThe main analysis produced a non-significant overall effect size; however, our most interesting finding was that results varied by age group. We explore this as well as difference by outcome type and the relation of the gene studied to dopamine.ConclusionOur findings vary by age group. However, due to heterogeneity we recommend more studies to answer some questions about a broader range of neurotransmitters, to include younger age groups, and to clarify difference by outcome type. We discuss issues of relevance to researchers to guide future meta-analyses.Systematic review registrationProspero: International prospective register of systematic reviews. Available from: https://www.crd.york.ac.uk/PROSPERO/view/CRD42018090220.